2020
DOI: 10.1177/0894439320909446
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phones Will Not Eliminate Digital and Social Divides: How Variation in Internet Activities Mediates the Relationship Between Type of Internet Access and Local Social Capital in Detroit

Abstract: This study examines the relationship between mode of Internet access, variety of online activities, and the potential for the Internet to contribute to local social capital in distressed, urban communities. Based on a sample of 525 telephone surveys in Detroit, findings show that breadth of access predicts participation in a larger variety of online activities, which is associated with higher levels of local social capital. Neither public Internet access, home broadband, nor Internet access through a mobile ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 100 publications
0
51
0
Order By: Relevance
“…Online service provisioning in key basic needs activity areas, such as health, education, public transit, government, and retail services, compounds the necessity of household internet services for TCHC residents. Though community intermediaries, such as public libraries and local coffee shops, play an important role in filling connectivity gaps for communities faced with precarious access to the internet, this support is both temporary, excludable, and primarily utilized for short-term access needs and discrete internet tasks (Reisdorf et al, 2020;Rhinesmith et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Online service provisioning in key basic needs activity areas, such as health, education, public transit, government, and retail services, compounds the necessity of household internet services for TCHC residents. Though community intermediaries, such as public libraries and local coffee shops, play an important role in filling connectivity gaps for communities faced with precarious access to the internet, this support is both temporary, excludable, and primarily utilized for short-term access needs and discrete internet tasks (Reisdorf et al, 2020;Rhinesmith et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, low-income households with broadband access demonstrate a breadth of instrumental online activities including education and job seeking, and place a high value on remaining connected despite financial constraints. Similarly, Reisdorf et al (2020) dismantle criticisms of low-income community members engaging in a limited breadth of online activities by demonstrating that the nature of activities performed online are more closely associated with the connection modality itself (mobile versus fixed, public versus at-home). Affordability barriers can press individuals into having to choose between one modality over another; subsequently limiting the breadth of online activities they can pursue.…”
Section: Rationale and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradations in what internet users can do with their access vary with regards to their socio-demographic background and offline resources (Helsper, 2012;Livingstone & Helsper, 2007), what kinds of devices they can afford and maintain (Gonzales, 2016), where they can access the internet, e.g., whether they are depending on mobile data plans or access through an internet service provider (Reisdorf et al, 2020), and other factors, such as digital skills (van Deursen & van Dijk, 2011) or attitudes toward technologies in general (Dutton & Reisdorf, 2019). Accordingly, digital inclusion activities cannot follow a one-size-fits-all approach-especially when we move the focus beyond the US or European context.…”
Section: Digital Inclusionmentioning
confidence: 99%
“…This research has shown that first-level divides (material access), second-level divides (skills and uses), and third-level divides (outcomes of differentiated access and use) persist, even in well-connected countries where the majority of the population is online (e.g., van Deursen, Helsper, Eynon, & van Dijk, 2017). Other studies have shown that mobile Internet access can help many people access the Internet in countries that lack wireline infrastructure-so-called mobile leapfroggingalbeit allowing a narrower range of activities and skills in comparison to access from a variety of devices (e.g., Reisdorf, Fernandez, Hampton, Shin, & Dutton, 2020;Tsetsi & Rains, 2017). Whereas we know quite a lot about what is lacking and for whom-which has become especially apparent during the current COVID-19 pandemicthere is less focus on what works to alleviate these inequalities and divides in a variety of cultural contexts.…”
Section: Introductionmentioning
confidence: 99%